Improving employee performance through employee engagement and self-efficacy with job satisfaction as an intervening variable - M. Trihudiyatmanto; Slamet Mujiyono; Eko Prawoto (Universitas Pekalongan, 2025)
This study examines the effect of employee engagement and self-efficacy on employee performance through job satisfaction as an intervening variable. The research method used in this study is quantitative, and questionnaire data collection was done using a Likert scale. The population and sample used in this study were all employees of PT. Cebong Imelindo Wonosobo, totaling 201 respondents. The data analysis technique in this study is the Structural Equation Modeling (SEM) technique on the Smart/PLS 4.1.0.3 program to test the outer and inner model coefficients. The results of this study indicate that employee engagement and self-efficacy have a positive and significant effect on employee performance. Employee engagement and self-efficacy have a positive and significant impact on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction has a positive and significant impact in mediating employee engagement and self-efficacy on employee performance. Practically, this study can provide an overview of the problems and focus on solving employee performance through employee engagement and self-efficacy, especially in the Cebong Imelindo Wonosobo company.